English Tasks For Communicative Competence Development: A Content Analysis Of When English Rings A Bell For Junior High School Based On Curriculum 2013 - Purnaningtyas, Wahyu, Prof. Dr. Endang Fauziati, M. Hum, Mauly Halwat Hikmat, Ph.D (2016)
Wahyu Purnaningtyas. S 200140020. THE TEXTBOOK ENTITLED 'WHEN ENGLISH RINGS A BELL' IS NOT ENOUGH TO DEVELOP THE STUDENTS' COMMUNICATIVE COMPETENCE OF JUNIOR HIGH SCHOOL. Thesis. Universitas Muhammadiyah Surakarta. 2016. This research is about the analysis of the tasks in the textbook related to five components of communicative competence. The objectives of this study are to explain what English tasks are designed for five components of communicative competence development reflected in English textbook and what are the frequency and the dominant type of task in each competence. This research is qualitative research. The data are the tasks from the textbook entitled 'When English Rings A Bell'. To collect the data, the researcher uses documentation method by doing some steps: read and understand the entire tasks in the textbook for several times; mark the tasks that are including in five components of communicative competence; type the tasks and code the marked tasks by writing the task number, the chapter, and the page of the tasks; account the tasks that develop the competences. The data were analysed by the theory of communicative competence suggested by Celce-Murcia et al (1995) and analysed by using interactive model of Huberman and Miles (1994). There are three steps in analysing the data; those are data reduction, data display, and conclusion drawing/verification. The result shows that the textbook entitled When English Rings A Bell consists of 181 tasks and there are three components of communicative competence (linguistic, actional, discourse) that developed the tasks. The English tasks that are designed to develop students' discourse competence are cohesion, deixis, coherence, genre, and conversational structure. The English tasks that are designed to develop students' linguistic competence are syntax, lexicon, phonology, and orthography. In actional competence, there are knowledge of language functions includes interpersonal exchange, information, feeling, opinion, and future scenario. The frequency of the English tasks designed for discourse competence is 55, 25%, for linguistic competence is 27, 07%, and for actional competence is 17, 68%. There are two competences that are not covered in the textbook, namely strategic competence and sociocultural competence. The dominant types of task for discourse competence is genre, for linguistic competence is phonology, and for actional competence is knowledge of language function especially information.